AUDITORÍA DE GESTIÓN AL TALENTO HUMANO DE LA COOPERATIVA DE TRANSPORTES LOJA “CASA MATRÍZ” PERIODO 2017 - Muñoz Alejandro, Briggette Estefanía (2020)
The development of the thesis: "HUMAN TALENT MANAGEMENT AUDIT OF THE TRANSPORTES LOJA COOPERATIVE" CASA MATRIZ "PERIOD 2017", is oriented to the application of the management audit, to establish the degree of control that the Cooperative maintains in the activities administrative and operational, through the application of indicators to measure the efficiency, effectiveness and economy with which resources are handled, also allows to verify compliance with laws, rules and regulations in the development of activities and issue a report where contain comments conclusions and recommendations that must be met for the development of the Cooperative. In the process of the management audit, the four phases were complied with, starting with the previous visit to the entity under study and an evaluation of internal control, elements that served to direct the audit techniques and procedures used in the development of the work, with which necessary evidence was obtained that supported the criteria spread in each one of the found findings. Additionally, management indicators were applied to evaluate the efficiency, effectiveness and economy of the human talent of the Transports Loja Cooperative. Finally, prepare a management audit report where conclusions are established and recommendations, the same ones that will be put to consideration by the highest authority to take the necessary corrective measures.